2019
DOI: 10.3390/cryst9010039
|View full text |Cite
|
Sign up to set email alerts
|

Tripling the Optical Efficiency of Color-Converted Micro-LED Displays with Funnel-Tube Array

Abstract: Color-converted micro-LED displays consist of a mono-color micro-LED array and color conversion materials to achieve full color, while relieving the burden of epitaxial growth of three-color micro-LEDs. However, it usually suffers from low efficiency and color crosstalk due to the limited optical density of color conversion materials. With funnel-tube array, the optical efficiency of the color-converted micro-LED display can be improved by ~3X, while the crosstalk is eliminated. After optimization of the tappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…To improve light efficiency and eliminate color crosstalk of color-converted micro-LED displays, Gou et al have proposed a funnel-tube array design in color-converted micro-LED displays with color filter [66]. Based on device simulation and modeling, it was found that by using funnel-tube array to confine phosphors inside each subpixel, the optical efficiency of the micro-LED display can be improved by ~3 times, while the crosstalk is eliminated.…”
Section: Full-color Schemesmentioning
confidence: 99%
“…To improve light efficiency and eliminate color crosstalk of color-converted micro-LED displays, Gou et al have proposed a funnel-tube array design in color-converted micro-LED displays with color filter [66]. Based on device simulation and modeling, it was found that by using funnel-tube array to confine phosphors inside each subpixel, the optical efficiency of the micro-LED display can be improved by ~3 times, while the crosstalk is eliminated.…”
Section: Full-color Schemesmentioning
confidence: 99%
“…The second receiver is able to receive light from the whole panel, and the collected light intensity is P total . The color crosstalk ratio is defined as R crosstalk , which can be calculated using the following Equation 7 [20,21].…”
Section: Optical Simulation For Gan Based Micro-led With Qds Filmmentioning
confidence: 99%
“…Although only the RGB subpixels inside the white dashed lines are turned on, light leakage outside this region is clearly observed. This problem becomes more severe as the phosphor film gets thicker …”
Section: Device Structurementioning
confidence: 99%
“…This problem becomes more severe as the phosphor film gets thicker. 14,15 To eliminate color crosstalk, we propose a funnel tube array with taper angles α and β (Device 2) as illustrated in Figure 3A and 3B. It is formed above micro-LED layer while the tube region aligned with each subpixel.…”
Section: Device Structurementioning
confidence: 99%